Solving a harvest scheduling optimization problem with constraints on clearcut area and clearcut proximity - Martins, Isabel; Alvelos, Filipe; Cerveira, Adelaide; Kašpar, Jan; Marušák, Robert (International transactions in operational research, 2023)
This study aims at solving a harvesting scheduling optimization problem with constraints on the clearcut area with additional constraints on clearcut proximity. The objective function is defined as the net present value generated by harvesting discounted by a penalty for each clearcut. This problem arises to reduce the negative environmental impact of excessive harvesting. We propose the connected‐bucket model, the so‐called bucket model with additional constraints on bucket connectivity and two definitions of stand adjacency, and a Dantzig–Wolfe decomposition. The decomposed model is solved by branch‐and‐price and the connected‐bucket model by a general‐purpose mixed integer programming solver (CPLEX). We compare the quality of the solutions obtained with both approaches for real instances. The branch‐and‐price approach found better solutions for the majority of the instances.